A Meta‐Regression of 18 Wildfire Chronosequences Reveals Key Environmental Drivers and Knowledge Gaps in the Boreal Nitrogen Balance - Stefan F. Hupperts; Frank Berninger; Han Y. H. Chen; Nicole Fenton; Mélanie Jean; Kajar Köster; Markku Larjavaara; Michelle C. Mack; Marie‐Charlotte Nilsson; Marjo Palviainen; Anatoly Prokushkin; Jukka Pumpanen; et al. (Global Change Biology, 2025)
Climate change has increased the size and frequency of wildfires across the boreal biome. Severe wildfires in boreal forests have been found to trigger shifts from evergreen to deciduous canopies, which has cascading effects on carbon and nitrogen cycling. Ecosystem productivity and carbon uptake in boreal forests are strongly linked with nitrogen, and Earth system models increasingly depend on our understanding of the nitrogen balance to predict post‐fire carbon uptake. To investigate the post‐fire boreal nitrogen balance, we combined a mass balance approach and literature synthesis to estimate rates of nitrogen accumulation and nitrogen inputs across a network of 18 boreal wildfire chronosequences that varied in both wildfire regime and post‐fire canopy type, comprising 527 forest stands. We found that deciduous‐ or mixed‐dominance boreal forests establishing after severe, stand‐replacing fires had the highest nitrogen accumulation rates (15.7 ± 3.8 kg ha −1 year −1 ), while evergreen‐dominated forests establishing after surface‐ or mixed‐severity fires had the lowest nitrogen accumulation rates (1.4 ± 1.1 kg ha −1 year −1 ). Annual known inputs from nitrogen deposition and biological nitrogen fixation combined, estimated from published data, largely failed to explain the rate of nitrogen accumulation, particularly in deciduous or mixed‐dominance forests establishing after stand‐replacing fires, suggesting that the origins of most nitrogen in these forest types remain poorly understood. As the frequency of severe wildfires increases across the boreal biome and shifts toward deciduous canopies become more common, our study reveals a large knowledge gap in the resulting nitrogen balance that needs to be resolved in order to improve predictions of forest carbon uptake.

The Interactive Role of Climatic Transfer Distance and Overstory Retention on Douglas‐Fir Seedling Survival and Height Growth in Interior British Columbia - Thomson C. Harris; W. Jean Roach; Erin M. Miller; Suzanne W. Simard (Global Change Biology, 2025)
The future climatic niche of interior Douglas‐fir ( Pseudotsuga menziesii var. glauca [Mirb.] Franco) is expected to have little spatial overlap with its current range due to climate change. The resulting misalignment of the climatic niche and species distribution is expected to result in many forests becoming maladapted in their current location, thus increasing vulnerability to disturbance and reducing productivity. This novel study examined the individual and interactive effects of climatic transfer distance and silviculture systems on planted 3‐year‐old Douglas‐fir seedlings across the natural range of interior Douglas‐fir in British Columbia. Several climatic transfer distance variables were considered, and the silviculture systems tested comprised the following gradients of tree retention: 0% retention (clearcut), 10% dispersed retention (seed‐tree), 30% aggregate retention, and 60% aggregate retention with thinning from below. Using linear mixed effect models, we found that survival and height were positively correlated with movements of seedlings to warmer, wetter, and more humid climates. Moisture availability had a stronger influence than temperature, indicating that seedlings transferred to warmer but more arid climates would experience decreased survival and height. Where seedlings were transferred to climates with greater frost frequency or decreased humidity, greater retention of overstory trees improved survival and height. Conversely, movements to more favorable climatic conditions (warmer and wetter) resulted in improved survival and height where overstory retention was low. Our findings suggest that genetic reshuffling of populations through assisted migration could benefit from overstory retention where stressful climatic conditions due to aridity or increased frost frequency occur.

Human dimensions in shellcraft: tool ownership differentiates taxa utilised and products produced - Thane A. Militz; Nittya S. M. Simard; Jeff Kinch; Paul C. Southgate (Frontiers in Marine Science, 2024)
Throughout the Pacific Islands, shellcraft has begun to feature prominently in development intervention which aims to generate positive livelihood outcomes for coastal communities. This activity often involves the post-harvest processing of natural assets, namely shells and skeletal remains of marine taxa, into jewellery by individuals or small-sized enterprises. To foster participation in shellcraft, development intervention commonly involves gifting or subsidising physical assets. Yet knowledge of the natural (i.e., taxa) and physical (i.e., tools) assets required for shellcraft remains scant. An understanding of human dimensions in shellcraft pertaining to patterns in asset use, such as how tool ownership differentiates taxa utilised and products produced, is important for determining if access to a specific tool is necessary, or an encumbrance, for achieving a desired outcome. In this study, we identified tools used and variation in tool ownership among artisans engaged in shellcraft to afford an accurate and realistic understanding of the tools required to participate in this activity. We then evaluate how ownership of a specific tool or type of tool differentiates both taxa utilisation and product production for shellcraft. Results indicate ownership of neither all nor any specific tool was required to participate in shellcraft, with artisans typically owning a unique combination of tools. Furthermore, results identified that some specific tools were critical for affecting the attractiveness of utilising certain taxa or producing certain products. Implications of the significant relationships between specific tools and certain taxa or products are discussed in the context of development intervention and commonly articulated theories of change where shellcraft is linked to subsistence fishing, aquaculture, or tourism.

A regional map of mangrove extent for Myanmar, Thailand, and Cambodia shows losses of 44% by 1996 - Priscilla Baltezar; Paulo J. Murillo-Sandoval; Kyle C. Cavanaugh; Cheryl Doughty; David Lagomasino; Thida Tieng; Marc Simard; Temilola Fatoyinbo (Frontiers in Marine Science, 2023)
Southeast Asia is home to some of the planet’s most carbon-dense and biodiverse mangrove ecosystems. There is still much uncertainty with regards to the timing and magnitude of changes in mangrove cover over the past 50 years. While there are several regional to global maps of mangrove extent in Southeast Asia over the past two decades, data prior to the mid-1990s is limited due to the scarcity of Earth Observation (EO) data of sufficient quality and the historical limitations to publicly available EO. Due to this literature gap and research demand in Southeast Asia, we conducted a classification of mangrove extent using Landsat 1-2 MSS Tier 2 data from 1972 to 1977 for three Southeast Asian countries: Myanmar, Thailand, and Cambodia. Mangrove extent land cover maps were generated using a Random Forest machine learning algorithm that effectively mapped a total of 15,420.51 km 2 . Accuracy assessments indicated that the classification for the mangrove and non-mangrove class had a producer’s accuracy of 80% and 98% user’s accuracy of 90% and 96%, and an overall accuracy of 95%. We found a decline of 6,830 km 2 between the 1970s and 2020, showing that 44% of the mangrove area in these countries has been lost in the past 48 years. Most of this loss occurred between the 1970s and 1996; rates of deforestation declined dramatically after 1996. This study also elaborated on the nature of mangrove change within the context of the social and political ecology of each case study country. We urge the remote sensing community to empathetically consider the local need of those who depend on mangrove resources when discussing mangrove loss drivers.

Utilization of marine taxa within an artisanal shellcraft sector of the Indo-Pacific region - Nittya S. M. Simard; Thane A. Militz; Jeff Kinch; Paul C. Southgate (Frontiers in Marine Science, 2022)
Sustainable utilization of marine taxa is critical for maximizing social and economic goals of livelihood development within the Indo-Pacific. Yet, despite an increasing importance of shellcraft as a livelihood activity within the Indo-Pacific, information on the taxa utilized within shellcraft sectors remains scant. To address this knowledge gap, our study examined diversity, in terms of composition and quantities, of marine taxa utilized by artisan households and, collectively, within an artisanal shellcraft sector of Papua New Guinea. For each taxon, critical source habitats were identified, and the geographic scale of exploitation established. Critically, presented data revealed 73 taxa, representing at least 77 species, were utilized within the studied sector. Many of the taxa utilized had not previously been linked to shellcraft sectors, demonstrating that a broader composition of taxa is utilized than previously acknowledged. In terms of quantity, annual utilization within the sector was close to 500,000 individuals, the majority being mollusks of either class Gastropoda (83.6%), represented by 37 genera, or class Bivalvia (9.6%), represented by four genera. There was a strong bias towards a particular species, Chrysostoma paradoxum (78.5% of all individuals), as indicated by indices for the diversity utilized ( H ′ = 1.23; D = 0.38). However, substantial variation was evident in the diversity of taxa utilized among households ( n = 36) engaged in shellcraft ( H ′ = 1.09 ± 0.71; D = 0.43 ± 0.27), with each household utilizing a unique composition of 19.1 ± 10.6 taxa. Source habitats for taxa ranged from pelagic to benthic intertidal and subtidal substrates, with the geographic scale of exploitation extending to 34 discrete locations up to 417 km away. The array of sector, household, and taxon-specific information presented provides a basis for supporting greater sustainability within shellcraft sectors across the Indo-Pacific, which is discussed within a context of informing community-based resource management, further developing marine aquaculture, and strengthening existing governance.

From Past to Present: Construction of a Dataset Documenting Mother-of-Pearl Exports From a Pacific Island Nation, Papua New Guinea - Nittya S. M. Simard; Thane A. Militz; Jeff Kinch; Paul C. Southgate (Frontiers in Marine Science, 2021)

Water resource development and sturgeon (Acipenseridae): state of the science and research gaps related to fish passage, entrainment, impingement and behavioural guidance - S. J. Cooke; J. J. Cech; D. M. Glassman; J. Simard; S. Louttit; R. J. Lennox; L. Cruz-Font; C. M. O’Connor (Reviews in Fish Biology and Fisheries, 2020)

Assessment of recreational boating as a vector for marine non-indigenous species on the Atlantic coast of Canada - M. Pelletier-Rousseau; R. Bernier; C. Clarke Murray; D. Drolet; A. Lacoursière-Roussel; A. Locke; J. L. Martin; C. H. McKenzie; C. W. McKindsey; T. W. Therriault; N. Simard (Biological Invasions, 2019)

Artisanal, shell-based handicraft in Papua New Guinea: Challenges and opportunities for livelihoods development - Nittya S. Simard; Thane A. Militz; Jeff Kinch; Paul C. Southgate (Ambio, 2019)

Association of genetic susceptibility variants for type 2 diabetes with breast cancer risk in women of European ancestry - Zhiguo Zhao; Wanqing Wen; Kyriaki Michailidou; Manjeet K. Bolla; Qin Wang; Ben Zhang; Jirong Long; Xiao-Ou Shu; Marjanka K. Schmidt; Roger L. Milne; Montserrat García-Closas; Jenny Chang-Claude; et al. (Cancer Causes & Control, 2016)

Genetic variation in the immunosuppression pathway genes and breast cancer susceptibility: a pooled analysis of 42,510 cases and 40,577 controls from the Breast Cancer Association Consortium - Jieping Lei; Anja Rudolph; Kirsten B. Moysich; Sabine Behrens; Ellen L. Goode; Manjeet K. Bolla; Joe Dennis; Alison M. Dunning; Douglas F. Easton; Qin Wang; Javier Benitez; John L. Hopper; et al. (Human Genetics, 2016)

Temporal and spatial mapping of red grouper Epinephelus morio sound production - C. C. Wall; P. Simard; M. Lindemuth; C. Lembke; D. F. Naar; C. Hu; B. B. Barnes; F. E. Muller‐Karger; D. A. Mann (Journal of Fish Biology, 2014)
The goals of this project were to determine the daily, seasonal and spatial patterns of red grouper Epinephelus morio sound production on the West Florida Shelf ( WFS ) using passive acoustics. An 11 month time series of acoustic data from fixed recorders deployed at a known E. morio aggregation site showed that E. morio produce sounds throughout the day and during all months of the year. Increased calling (number of files containing E. morio sound) was correlated to sunrise and sunset, and peaked in late summer (July and August) and early winter (November and December). Due to the ubiquitous production of sound, large‐scale spatial mapping across the WFS of E. morio sound production was feasible using recordings from shorter duration‐fixed location recorders and autonomous underwater vehicles ( AUVs ). Epinephelus morio were primarily recorded in waters 15–93 m deep, with increased sound production detected in hard bottom areas and within the Steamboat Lumps Marine Protected Area (Steamboat Lumps). AUV tracks through Steamboat Lumps, an offshore marine reserve where E. morio hole excavations have been previously mapped, showed that hydrophone‐integrated AUVs could accurately map the location of soniferous fish over spatial scales of

Insertion polymorphism of transposable elements and population structure of Anopheles gambiae M and S molecular forms in Cameroon - M. BOULESTEIX; F. SIMARD; C. ANTONIO‐NKONDJIO; H. P. AWONO‐AMBENE; D. FONTENILLE; C. BIÉMONT (Molecular Ecology, 2007)
The insertion polymorphism of five transposable element (TE) families was studied by Southern blots in several populations of the M and S molecular forms of the mosquito Anopheles gambiae sensu stricto from southern Cameroon. We showed that the mean TE insertion site number and the within‐population insertion site polymorphism globally differed between the M and S molecular forms. The comparison of the TE insertion profiles of the populations revealed a significant differentiation between these two molecular forms (0.163 ST

Impact of insecticide‐treated bed nets implementation on the genetic structure of Anopheles arabiensis in an area of irrigated rice fields in the Sahelian region of Cameroon - C. WONDJI; F. SIMARD; T. LEHMANN; E. FONDJO; A. SAMÈ‐EKOBO; D. FONTENILLE (Molecular Ecology, 2005)
Variation at 12 microsatellite loci was investigated to assess the impact of the implementation of insecticide‐treated bed nets (ITNs) on the genetic structure of Anopheles arabiensis in Simatou, a village surrounded by irrigated rice fields in the Sahelian area of Cameroon. The An. arabiensis population of Simatou was sampled twice before ITN implementation, and twice after. Effective population size estimates ( N e ) were similar across each time point, except for the period closely following ITN introduction where a nonsignificant reduction was recorded. Hence, we believe that ITN implementation resulted in a temporary bottleneck, rapidly followed by a demographic expansion. The genetic diversity of the population was not significantly affected since different genetic parameters (allele number, observed and expected heterozygosities) remained stable. Low estimates of genetic differentiation between the populations from Simatou and Lagdo, separated by 300 km, suggested extensive gene flow among populations of An. arabiensis in the Sahelian region of Cameroon. A decrease in the susceptibility to deltamethrin was observed following ITN introduction, but no kdr mutation was detected and a metabolic resistance mechanism is probably involved. The temporary effect of ITNs on the genetic structure of An. arabiensis population suggests that, to optimize the success of any control programme of this species based on ITNs, the control area should be very large and the programme should be implemented for a long period of time.

Hybridization between transgenic Brassica napus L. and its wild relatives: Brassica rapa L., Raphanus raphanistrum L., Sinapis arvensis L., and Erucastrum gallicum (Willd.) O.E. Schulz - S. I. Warwick; M.-J. Simard; A. Légère; H. J. Beckie; L. Braun; B. Zhu; P. Mason; G. Séguin-Swartz; C. N. Stewart (Theoretical and Applied Genetics, 2003)

Role of the UL28 homologue of bovine herpesvirus 1 in viral DNA cleavage and packaging - N. Desloges; C. Simard (Archives of Virology, 2003)

Mapping of the bovine herpesvirus 1 glycoprotein C promoter region and its specific transactivation by the viral BICP27 gene product - F. Hamel; C. Simard (Archives of Virology, 2003)

Bovine Immunodeficiency Virus in Relation to Embryos Fertilized In Vitro - A. Bielanski; C. Simard; P. Maxwell; S. Nadin-Davis (Veterinary Research Communications, 2001)

Expression kinetics of the late UL12 gene encoding the bovine herpesvirus 1 alkaline nuclease - N. Desloges; C. Simard (Archives of Virology, 2001)

Transcriptional and translational expression kinetics of the UL25 homologue of bovine herpesvirus 1.1 - N. Desloges; H. Boucher; C. Simard (Archives of Virology, 2001)

SMN gene duplication and the emergence of the SMN2 gene occurred in distinct hominids: SMN2 is unique to Homo sapiens - C. Rochette; N. Gilbert; L. Simard (Human Genetics, 2001)

Genetic Determinants of Pseudomonas aeruginosa Colonization in Cystic Fibrosis Patients in Canada - M. De Braekeleer; C. Allard; J.-P. Leblanc; G. Aubin; F. Simard (European Journal of Clinical Microbiology & Infectious Diseases, 1998)

Genetic determinants ofPseudomonas aeruginosa colonization in cystic fibrosis patients in Canada - M. Braekeleer; C. Allard; J. -P. Leblanc; G. Aubin; F. Simard (European Journal of Clinical Microbiology & Infectious Diseases, 1998)

s of papers presented at the 81st annual meeting of The Potato Association of America Charlottetown, P.E.I., Canada August 3 – 7, 1997 - S. T. Ali-Khan; C. Hetner; L. Ladislav; V. Currie; Walter J. Arsenault; A. Naseer Aziz; Janet E. A. Seabrook; George C. C. Tai; J. B. Bamberg; Alfonso H. del Rio; Max Martin; J. B. Bamberg; et al. (American Journal of Potato Research, 1997)

Synthetic peptides corresponding to the F protein of RSV stimulate murine B and T cells but fail to confer protection - M. Trudel; E. J. Stott; G. Taylor; D. Oth; G. Mercier; F. Nadon; C. Séguin; C. Simard; M. Lacroix (Archives of Virology, 1991)

Gene mapping of infectious bovine rhinotracheitis viral DNA genome - Claire Simard; Francine Nadon; Ccile Sguin; Sylvie LaBoissire; M. Trudel (Archives of Virology, 1990)

Comparison of caprine, human and bovine strains of respiratory syncytial virus - M. Trudel; F. Nadon; C. Simard; F. Bélanger; R. Alain; C. Séguin; G. Lussier (Archives of Virology, 1989)